Online Features of Qzone Weblog for Critical Peer Feedback to Facilitate Business English Writing. (December 2016) - Gao, Xianwei; Samuel, Moses; Asmawi, Adelina
Qzone weblog is one of the most popular weblogs in China. This study explores Qzone weblog for critical peer feedback to facilitate Business English writing among the Chinese undergraduates. A qualitative case study is conducted by NVivo 8 to analyze the three research data of semistructured interviews, Business English writing assignments, and critical peer feedback artifacts. Three research questions are focused on the case participants' perception of this study, the strength and weakness of Qzone for critical peer feedback, and online features of Qzone affecting critical peer feedback in Business English writing. The findings indicate that Qzone weblog is a convenient information communication technology platform for online critical peer feedback among the Chinese undergraduates. The six aspects of strength and five online features are coded by NVivo 8, which are models by NVivo 8 with figures. The weakness of Qzone is the character number limitation for blogging and feedback. The conclusion of this study will be applied for the use of Qzone weblog and other kinds of weblog for online peer feedback in English writing.